Lysozyme from Chicken Egg White as an Antibacterial Agent - Harsi Dewantari Kusumaningrum; Syahrizal Nasution; E Kusumaningtyas; D N Faridah (Indonesian Center for Animal Research and Development, 2018)
Lysozyme is one of the constituent proteins of chicken egg white that plays an important role in a protection system during the embryo growing process. Lysozyme protection systems can be applied in food and for health. This paper aims to describe the role of egg white lysozyme which has the antibacterial activity to improve food safety and health. Mechanism and activity of lysozyme protection can be explored by understanding the structure of proteins, type of amino acids, and the sequence of amino acids. The mechanism of lysozyme antibacterial activity against Gram positive bacteria occurs through its ability to breakdown the peptidoglycan glycosidic bonds in the bacterial cell wall membrane. The antibacterial activity of lysozyme can be increased when its normal lysozyme form was denatured/hydrolyzed through modifying the lysozyme structure by heat and enzymatic treatment. Heat treatment will reveal the active site of lysozyme after denaturation, leading to the destruction of the bacterial cell wall membrane. Enzymatic treatment through hydrolysis process of hydrolysis by protease enzymes will generate antibacterial peptides, which have the ability to inhibit the growth of Gram positive bacteria and Gram negative bacteria. Antibacterial lysozyme peptides and heat treated lysozyme are dominated by hydrophobic amino acids and positively charged to facilitate interaction between lysozyme and lipopolysaccharide which coats peptidoglycan. Antibacterial lysozyme peptide can be used as an antibiotic and a safe natural preservative compared to synthetic material and can reduce the risk of destructive bacteria and pathogenic bacteria. Lysozyme peptide is potential to protect human health since it has also other activities such as inhibition of angiotensin-converting enzyme, antihypertensive, antitumor, antioxidant, and antiviral agents.